Pediatric resident firearm-related anticipatory guidance: Why are we still not talking about guns? - Hoops, Katherine (Prev Med, 2019)
This study characterizes the current firearm-related anticipatory guidance practices of pediatricians-in-training and the factors affecting those practices. In this study of Pediatric residents in the Mid-Atlantic region, surveys were distributed to 189 trainees at three hospitals. Eighty-one responses were collected between June 2017 and March 2018. The survey gathered information about the residents’ values related to firearms, firearm-specific counseling practices, barriers to providing counseling, and educational needs related to firearms. The residents surveyed overwhelmingly agreed (96%) that physicians have a responsibility to counsel patients on the risks posed by firearms. However, most (63%) never provide firearm-related counseling or do so in only 1–5% of well-child visits. Their unfamiliarity with safe storage devices contributes to a lack of comfort providing counseling. For pediatricians to provide potentially lifesaving counseling on firearm safety, they must be well-versed in the subject and feel comfortable and confident in doing so. Educational interventions addressing physician self-efficacy are necessary to accomplish this. There is an urgent need to develop a comprehensive firearm safety education program for physicians and trainees to improve firearm counseling.